The Existence of the Death Penalty in Indonesia: History Debates and Legal Developments - Ardhana, Rizky Owen; Lubis, Syofiaty (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2023)
Death penalty is a punishment that has long been a controversial topic in Indonesia. Although it still exists, the existence of death penalty in Indonesia has undergone various changes and discussions that evolve along with the development of society and law in this country. This abstract aims to present an overview of the existence of death penalty in Indonesia. The history of death penalty in Indonesia can be traced back to the Dutch colonial period, where this punishment was applied as part of the colonial legal system. After independence, Indonesia inherited the death penalty law from the Dutch colonizers and maintained it as one of the forms of punishment in the criminal justice system. Although still applied, the existence of the death penalty in Indonesia has drawn various criticisms from within and outside the country. Critics highlight issues such as the potential for irreparable legal errors, selective justice, and human rights violations. However, on the other hand, there is also support for the death penalty as a form of punishment that is considered effective in suppressing serious crimes and providing a deterrent effect to criminals. Over the past few years, there has been a shift in the views of the public and government in relation to the death penalty. Although it still exists, its use has become more limited and restrained. Several steps have been taken, including a moratorium on death penalty executions and revision of the Death Penalty Law. The debate on the existence of the death penalty in Indonesia also takes into account issues such as humanity, justice, and effectiveness as a punishment. Some parties argue that the abolition of the death penalty is more in line with humanitarian values and the protection of human rights, while others still maintain this punishment as a form of justice for victims of crime. Thus, the existence of the death penalty in Indonesia is a complex and evolving subject, influenced by factors such as legal developments, societal values, and pressure from the international community. Death penalty remains a challenging issue for Indonesia in finding a balance between justice, humanity, and effectiveness in law enforcement.